Using Musculoskeletal Models to Estimate in vivo Total Knee Replacement Kinematics and Loads: Effect of Differences Between Models - Curreli, Cristina; Di Puccio, Francesca; Davico, Giorgio; Modenese, Luca; Viceconti, Marco (Frontiers in Bioengineering and Biotechnology, 2021)
Total knee replacement is one of the most performed orthopaedic surgeries to treat knee joint diseases in the elderly population. Although the survivorship of knee implants may extend beyond two decades, the poor outcome rate remains considerable. A recent computational approach used to better understand failure modes and improve total knee replacement outcomes is based on the combination of musculoskeletal and finite element models. This combined multiscale modelling approach is a promising strategy in the field of computational biomechanics; however, some critical aspects need to be investigated. In particular, the identification and quantification of the uncertainties related to the boundary conditions used as inputs to the finite element model due to a different definition of the musculoskeletal model is crucial. The aim of this work is therefore to investigate this problem, which is relevant for the model credibility assessment process. Three different generic musculoskeletal models available in the OpenSim platform, were used to simulate gait, based on experimental data from the fifth edition of the “Grand Challenge Competitions to Predict In Vivo Knee Loads”. The outputs of the musculoskeletal analyses were compared in terms of relative kinematics of the knee implant components and joint reaction forces and moments acting on the tibial insert. Additionally, the estimated knee joint reactions were compared with those measured by the instrumented knee implant so that the “global goodness of fit” was quantified for each model. Our results indicated that the different kinematic definition of the knee joint and the muscle model implemented in the different musculoskeletal models influenced both the motion and the load history of the artificial joint. The present work demonstrates the importance of examining the influence of the model assumptions on the output results and represents a first step for future studies that will investigate how the uncertainties in the musculoskeletal models propagate on disease specific finite element model results.